Structural densification of lithium phosphoaluminoborate glasses. Issue 3 (22nd November 2020) - Liu, Pengfei; Søndergaard, Andreas L. S.; Youngman, Randall E.; Rzoska, Sylwester J.; Bockowski, Michal; Jensen, Lars R.; Smedskjaer, Morten M.
Abstract: Lithium aluminoborate glasses have recently been found to undergo dramatic changes in their short‐range structures upon compression at moderate pressure (~1 GPa), most notably manifested in an increase in network forming cation coordination number (CN). This has important consequences for their mechanical behavior, and to further understand the structural densification mechanisms of this glass family, we here study the effect of P2 O5 incorporation in a lithium aluminoborate glass (with fixed Li/Al/B ratio) on the pressure‐induced changes in structure, density, and hardness. We find that P2 O5 addition results in a more open and soft network, with P‐O‐Al and P‐O‐B bonding, a slightly smaller fraction of tetrahedral‐to‐trigonal boron, and an unchanged aluminum speciation. Upon compression, the cation‐oxygen CNs of both boron and aluminum increase systemically, whereas the number of bridging oxygens around phosphorous ( Q n ) decreases. The glasses with higher P2 O5 content feature a larger decrease in Q n (P) upon compression, which leads to more non‐bridging oxygen that in turn fuel the larger increase in CN of B and Al for higher P2 O5 content. We find that the CN changes of Al and B can account for a large fraction (around 50% at 2 GPa) of the total volume densification and that the extent of structural changes (so‐called atomic self‐adaptivity) scales well with the extent of volume densification and pressure‐induced increase in hardness.